Wybór rady gromadzkiej w Wielkopolsce po uchwaleniu ustawy scaleniowej z 1933 roku - Podkowski, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
The Act of 23 March 1933 on the partial change of the local government system introduced the possibility of the formation of districts throughout the territory of the Republic of Poland, as the components of the rural municipality. The districts did not exist in the province of Poznań, which for more than a century was under Prussian occupation, as well as during the first years after regaining independence.The district council consisted of a village leader sołtys, who was its chairman, vice village leader podsołtys and councilors, the number of which was dependent on the number of residents of the district. The elections to the district councils were general, equal and direct. The elections of councilors and their deputies were envisaged by the district governor.The method of electing councilors was specified in the electoral rules of 1934, which was revised four years later. The preserved archive materials show that the provisions of the electoral rules were strictly adhered to by the electoral commissions.
Keywords: local government; rural commune